2022
DOI: 10.3389/fpubh.2022.908152
|View full text |Cite
|
Sign up to set email alerts
|

When Lack of Trust in the Government and in Scientists Reinforces Social Inequalities in Vaccination Against COVID-19

Abstract: ObjectiveTo assess whether lack of trust in the government and scientists reinforces social and racial inequalities in vaccination practices.DesignA follow-up of the EpiCov random population-based cohort survey.SettingIn July 2021, in France.ParticipantsEighty-thousand nine hundred and seventy-one participants aged 18 years and more.Main Outcome MeasuresAdjusted odds ratios of COVID-19 vaccination status (received at least one dose/ intends to get vaccinated/ does not know whether to get vaccinated/refuses vac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 53 publications
6
29
1
1
Order By: Relevance
“…These accessibility issues may also explain the association we find between lower vaccination rates and living in a district with a high proportion of immigrants, which may for instance reveal language barriers. These associations of lower vaccination rates with more poverty and with higher proportions of immigrants in the district of residence are compatible with the results of a survey conducted in July 2021 in France 16 on close to 81 000 participants, which indicated that unvaccinated respondents were more likely to have lower income and more likely to belong to ethnic minorities than vaccinated respondents.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These accessibility issues may also explain the association we find between lower vaccination rates and living in a district with a high proportion of immigrants, which may for instance reveal language barriers. These associations of lower vaccination rates with more poverty and with higher proportions of immigrants in the district of residence are compatible with the results of a survey conducted in July 2021 in France 16 on close to 81 000 participants, which indicated that unvaccinated respondents were more likely to have lower income and more likely to belong to ethnic minorities than vaccinated respondents.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, the effect of mistrust in the government on vaccination refusal was shown to be even stronger among individuals from lower social classes than from higher social classes. 16 Finally, our data do not inform directly on the reasons for non-vaccination—e.g. whether it is hesitancy, refusal, or accessibility issues, which is why our approach is complementary to qualitative surveys.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The second possible explanation as to why people with low health literacy neither trust nor use health professionals and health authorities for COVID-19 information is that individuals with low health literacy have low trust in scientists, especially during the COVID-19 pandemic [ 29 , 30 ]. For example, people with low health literacy tend to not embrace the COVID-19 vaccine, due to a lack of trust in the government and scientists that stems from the uncertain attitudes towards possible herd immunity, the complexity of the scientific and political discourse surrounding COVID-19 vaccines, as well as questions about the vaccination effectiveness as new variants keep evolving [ 29 ]. Additionally, official rules and recommendations for preventive measures (e.g., mask mandates) based on scientific findings and clinical trials keep changing, because of the evolving knowledge about how this virus is behaving [ 30 ], which leads to negative feelings, such as being overwhelmed, confused, upset, and scared [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When applying the teach-back technique, health care providers ask their patients to repeat, in their own words, what they have been told, using a caring tone of voice and attitude to create a “shame-free” environment for patients [ 35 ]. Third, collaborating closely with community organizations and social workers to create health messages with no political interference is another effective strategy for government agencies to utilize, in order to build trust in the public [ 29 , 36 ]. Another strategy for government agencies to maintain public trust is to ensure clear information and unambiguous health instructions related to COVID-19 that represent government transparency and effective communication [ 37 ].…”
Section: Discussionmentioning
confidence: 99%